IMPROVEMENT IN WHEAT (TRITICUM AESTIVUM L.) YIELD BY MANIPULATING SEED RATE AND ROW SPACING IN VEHARI ZONE - M. Ali; L. Ali; M. Sattar; M. A. Ali (Journal of Animal and Plant Sciences, 2010)
Seed rate and row spacing in a given area have marked effects on wheat yield components. Field experiments were conducted at Adaptive Research Farm, Vehari for a period of three years from 2005-06 to 2007-08 to investigate the impact of various seed rates and row spacings on the yield of wheat cv. Uqaab-2000. Four levels of seed rate (125, 150, 175 and 200 kg ha -1) and three row spacing (11.25, 15.00 and 22.50 cm) were tested in split plot design with seed rate in main plots and row spacing in sub plots. The results indicated that main effects of seed rate and row spacing affected number of tillers m-2, no. of grain spike-1, 1000 grain weight, grain yield and harvest index significantly (p<0.05) and different seed rates did not affect straw yield significantly in 2007-08. Three years average results indicated that maximum grain yield (4.13 t ha-1) was obtained where moderate seed rate of 150 kg ha-1 was used by planting wheat during second fortnight of November and 22.50 cm apart rows gave higher grain yield than 15.00 cm and 11.25 cm. Straw yield increased with the increase in seed rate and showed superiority of 11.25 cm over 15.00 cm and 22.50 cm row spacing.  Maximum harvest index values of 48.14% were recorded at seed rate of 150 kg ha-1 with 22.50 cm row spacing. Interaction between seed rate and row spacing was significant for no. of grain spike-1, 1000 grain weight, grain yield, straw yield and harvest index in 2005-06. There was significant relationship (R2=0.88, 0.99) between grain yield and harvest index at various seed rates and row spacing.
Keywords: Triticum aestivum; seed rate; row spacing; yield; Pakistan